Нормативне забезпечення права на інформацію в Україні: стан та пропозиції удосконалення - Ярмол, Лілія; Тимань, Марта; Yarmol, Liliia; Tyman, Marta (Видавництво Львівської політехніки, 2020)
Стаття присвячена висвітленню одного з найважливіших конституційних прав людини – права на інформацію, реалізація якого необхідна для забезпечення основних умов життєдіяльності людини. Під час дослідження використано загальнонаукові (функціональний, аксіологічний, порівняльний, логічний тощо) та спеціально-юридичні методи (тлумачення юридичних норм, функціонально-правовий, порівняльно-правовий тощо). Відзначено, що право людини на інформацію проголошене в основних міжнародних документах з прав людини (Загальна декларація прав людини (ст. 19), Міжнародний пакт про громадянські і політичні права (ст. 19), Конвенція про захист прав людини і основоположних свобод (ст. 10)). Щоправда, відповідно до зазначених міжнародних актів, це право виступає складовою частиною свободи вираження поглядів. В Україні на конституційному рівні проголошено право кожного “вільно збирати, зберігати, використовувати і поширювати інформацію усно, письмово або в інший спосіб – на свій вибір” (ч. 2 ст. 34 Конституції України). Окрім того, у нас прийнято й чимало нормативно-правових актів, присвячених реалізації, охороні та захисту права на інформацію. Однак вони потребують удосконалення, доповнення й узгодження між собою, з огляду на зміни в суспільному та, державному житті, а також у зв’язку зі стрімким розвитком інформаційних відносин у світі. Відтак для покращення механізму реалізації права на інформацію в Україні запропоновано: 1) у ч. 2 ст. 34 Конституції України передбачити і такі можливості особи: шукати, одержувати, фіксувати та передавати інформацію; 2) в окремому розділі Конституції, присвяченому правам дитини, проголосити такі важливі можливості дитини: свободу формування та вираження її поглядів (складовими якої є й інформаційні права), право бути вислуханою під час прийняття будь-яких рішень, що її стосуються; удосконалення. 3) у законодавстві про освіту конкретизувати можливості дитини щодо доступу, пошуку, отримання, поширення інформації в процесі здобуття нею освіти. Підтримано пропозицію вітчизняних науковців щодо кодифікації інформаційного законодавства та прийняття Інформаційного кодексу України, який сприяв би кращому юридичному забезпеченню права на інформацію.

The article is devoted to the coverage of one of the most important constitutional human rights– the right to information, the realization of which is necessary to ensure the basic conditions of human life. The purpose of the article is to analyze the normative provision of the right to information in Ukraine and to formulate proposals for its improvement. The research used general scientific (functional, axiological, comparative, logical, etc.) and special legal methods (interpretation of legal norms, functional law, comparative law, etc.). It is noted that the human right to information is enshrined in major international human rights instruments (Universal Declaration of Human Rights (Article 19), International Covenant on Civil and Political Rights (Article 19), Convention for the Protection of Human Rights and Fundamental Freedoms (Article 10). However, according to these international instruments, this right is an integral part of the freedom of expression. In Ukraine, at the constitutional level, the right of everyone is proclaimed as; “Everyone shall have the right to freely collect, store, use, and disseminate information by oral, written, or other means at his discretion.” (Part 2, Art. 34). In addition, we have adopted many regulations on the implementation, protection and defense of the right to information. However, they need to be improved, complemented and coordinated in the light of changes in public and in particular state life, and in view of the rapid development of information relations in the world. In order to improve the mechanism for exercising the right to information, the Constitution of Ukraine proposes: 1) in Part 2 of Art. 34 provide for the following capabilities of a person: seek, receive, capture, transmit information; 2) in a separate section on the rights of the child, to proclaim the following important opportunities for the child: freedom of formation and expression of its views (which also includes information rights), the right to be heard when making any decisions concerning it. 3) specify in the legislation on education the possibilities of the child to access, search, receive, disseminate information in the process of obtaining its education. The proposal of national scientists on the codification of information legislation and adoption of the Information Code of Ukraine, which would contribute to better legal protection of the right to information, was supporte
Regulatory provision of the right to information in Ukraine: the state and proposals of improvement
Keywords: право на інформацію; інформація; нормативне забезпечення; законодавство; міжнародні документи; пропозиції; right to information; information; regulatory support; legislation; international documents; proposals; 342.7